Climate change and forestry carbon sink: a literature review and visualization perspective - Zhang, Qiaomin; Song, Jianmin; Mayuka, Ruth Nzinga (Frontiers in Forests and Global Change, 2025)
Employing scientometric analysis of 8,346 peer-reviewed publications indexed in the Web of Science Core Collection (1981–2023) on climate change and forestry carbon sink, systematically elucidated fundamental dimensions encompassing developmental trajectories, disciplinary characteristics, and intellectual frameworks. The results of this study indicate the following: (1) the number of publications focusing on climate change and forestry carbon sink is exhibiting exponential growth, signifying a “Rapid development period” in this field. Forest Ecology and Management constitutes the predominant knowledge dissemination platform, while Environmental Sciences stands out as the most popular subject category. (2) The United States, China, and Canada are the most productive countries in terms of research output in this field. Additionally, the Chinese Academy of Sciences serves as a pivotal institutional entity in epistemological production conducting research in this area. (3) The seminal work, titled “A large and persistent carbon sink in the World’s forests” (Citations: 6,467) was authored by Pan, Y., a senior researcher affiliated with the U. S. Department of Agriculture (USDA) Forest Service. (4) The bibliometric keyword co-occurrence network analysis of keywords illustrates that climate change and forestry carbon sink remain the focal research topics in this field. It is observed that the research hotspot of climate change and forest carbon sink is transitioning from ecological dynamics to socio-economic systems research. Nonetheless, carbon reduction and carbon sink continue to be recognized as constituting essential components in the climate stabilization portfolio. Ultimately, drawing from the aforementioned analytical research, this paper suggests four prospective avenues for advancing the epistemic frontier.